Tribology properties of technical oils based on sunflower and rapeseed oils - Войтов, В.А.; Кравцов, А.Г. (Problems of Tribology, 2014)
The article discussed prospects of using vegetable oil as a basic raw material for the manufacture of lubricants and working fluids for hydraulic volume. The main physical-mechanical characteristics of Tribology and oils based on vegetable oils as compared to trade oil and synthetic. Determined the rate of wear model tribosystem using oils based on vegetable oils.